AWS Cloud Projects. - Ivo Pinto; Pedro Santos; PACKT (GB: Packt, 2024)
Build eight real-world applications and gain hands-on expertise with AWS services Key Features Gain hands-on experience in architecting, deploying, and managing AWS applications Build scalable, AI-powered, and serverless applications using AWS Lambda, DynamoDB, Amazon Rekognition, and more Master AWS infrastructure automation and DevOps workflows with CI/CD pipelines, CodePipeline, and QuickSight Purchase of the print or Kindle book includes a free PDF eBook Book Description Tired of resumes getting lost in the pile? This book is your roadmap to building an in-demand AWS portfolio that grabs attention and gets you hired. This comprehensive guide unlocks AWS's full potential through eight real-world projects designed for developers of all levels. Inside, you'll find invaluable guidance for crafting stunning websites with S3, CloudFront, and Route53. You'll build robust and scalable applications, such as recipe-sharing platforms, using DynamoDB and Elastic Load Balancing. For streamlined efficiency, the book will teach you how to develop serverless architectures with AWS Lambda and Cognito. Gradually, you'll infuse your projects with artificial intelligence by creating a photo analyzer powered by Amazon Rekognition. You'll also automate complex workflows for seamless content translation using Translate, CodePipeline, and CodeBuild. Later, you'll construct intelligent virtual assistants with Amazon Lex and Bedrock to answer web development queries. The book will also show you how to visualize your data with insightful dashboards built using Athena, Glue, and QuickSight. By the end of this book, you'll have a portfolio of AWS projects to showcase your cloud skills, making you stand out in today's competitive job market. What you will learn Develop a professional CV website while learning AWS fundamentals Build a recipe-sharing application using AWS's serverless toolkit Leverage AWS AI services to create a photo friendliness analyzer for professional profiles Implement a CI/CD pipeline to automate content translation across languages Develop an AI-powered Q&A chatbot using Amazon Lex and cutting-edge LLMs Build a business intelligence application to analyze website clickstream data and understand user behavior with AWS Who this book is for This book is ideal for students, software developers, and IT professionals looking to gain hands-on experience with AWS and transition into cloud computing. Whether you're new to AWS or expanding your cloud expertise, these projects will help you develop practical skills, apply real-world concepts, and follow industry best practices. A background in computer science or engineering and basic programming skills is recommended, but no prior AWS experience is required. Each project includes theoretical explanations of AWS services, ensuring that even beginners can follow along.
Data in extended ASCII character set.
Mode of access: Internet.